2013
DOI: 10.1186/1471-2431-13-117
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional study of the association of body composition and physical fitness with bone status in children and adolescents from 11 to 16 years old

Abstract: BackgroundThe aim of the study was to verify the association between body composition and physical fitness with bone status in children and adolescents.MethodsA cross-sectional study was conducted with 300 healthy students (148 boys, 152 girls). Weight, height, fat and fat-free mass, and percentage of body fat (%BF) were evaluated, as were physical fitness (abdominal exercise, flexibility, and horizontal jump tests) and maximum oxygen consumption. Bone parameters (amplitude-dependent speed of sound; AD-SoS) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 35 publications
1
16
0
8
Order By: Relevance
“…Minatto [118] 2013 cross-sectional n.a. De Moraes [182] 2013 cross-sectional n.a. Tucker [183] 2013 cross-sectional n.a.…”
Section: Muscular Endurancementioning
confidence: 99%
See 1 more Smart Citation
“…Minatto [118] 2013 cross-sectional n.a. De Moraes [182] 2013 cross-sectional n.a. Tucker [183] 2013 cross-sectional n.a.…”
Section: Muscular Endurancementioning
confidence: 99%
“…The review highlighted the sit and reach test with a number of 14 records found [63,118,128,139,[179][180][181][182][183][184][185][186] -the lowest point reached by the fingertips while standing on a box with legs extended with 1 record found [149], the V-sit and reach with 1 record found [187] and the shoulder stretches with 2 records found [117,188] (Table 6). …”
Section: Muscular Endurancementioning
confidence: 99%
“…Estos resultados coinciden con los reportados en otros estudios; por ejemplo, en un estudio de Estados Unidos en el que se compararon hombres y mujeres con edades entre los 17 y los 18 años, las mujeres registraron grados de adiposidad más elevados que los hombres (42). En otro estudio reciente en adolescentes brasileños de 11 a 16 años de edad y de ambos sexos (43), se encontró que el índice de masa corporal y el grado de grasa corporal fueron mayores en las chicas que en los chicos, aunque no se encontraron diferencias significativas entre los sexos a pesar de que la muestra analizada fue mucho más pequeña que la de este estudio (104 mujeres y 94 hombres).…”
Section: Discussionunclassified
“…Sin embargo, las mujeres suelen destacarse frente a los hombres en cuanto a la amplitud del movimiento articular, como se demostró en un estudio llevado a cabo en estudiantes brasileños de 11 a 16 años de edad (43). En este estudio también se compararon los grados de adiposidad y la condición física en función de la edad, pero en los hombres entre sí y las mujeres entre sí.…”
Section: Discussionunclassified
See 1 more Smart Citation